Thin film germanium on silicon created via ion implantation and oxide trapping. (May 2015) - Anthony, R; Knights, A P
Abstract: We present a novel process for integrating germanium with silicon-on-insulator (SOI) wafers. Germanium is implanted into SOI which is then oxidized, trapping the germanium between the two oxide layers (the grown oxide and the buried oxide). With careful control of the implantation and oxidation conditions this process creates a thin layer (current experiments indicate up to 20-30nm) of almost pure germanium. The layer can be used potentially for fabrication of integrated photo-detectors sensitive to infrared wavelengths, or may serve as a seed for further germanium growth. Results are presented from electron microscopy and Rutherford back-scattering analysis, as well as preliminary modelling using an analytical description of the process.